2006
DOI: 10.1007/bf02969422
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-cariogenic activity of dichloromethane fraction fromRheum undulatum L. root

Abstract: This study aimed to evaluate in vitro effects of Rheum undulatum L. root on the development of dental caries, especially its effects on viability, dental plaque formation, and glycolytic acid production of Streptococcus mutans and Streptococcus sobrinus. Methanol extract of Rheum undulatum L. root and its fractions were prepared and tested. Among the test extract and fractions, dichloromethane fraction (DF) showed the most active antibacterial activity (inhibition zone: 13-17 mm) against S. mutans and S. sobri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…Anthraquinones are important phytochemicals in rhubarb and were found to be highly inhibitory for P. gingivalis growth, more specifically aloe-emodin and rhein possessed an MIC of 0.75 mg/ml. The above results are in agreement with previous studies that showed that an anthraquinone-rich extract of another species of rhubarb (Rheum undulatum) exhibited antibacterial activity towards the cariogenic bacterium Streptococcus mutans (Song et al, 2006;Kim et al, 2011). Moreover, synergistic effects of anthraquinones (emodin, rhein) in combination with antibiotics (ampicillin, oxacillin) have been reported for methicillin-resistant Staphylococcus aureus (Joung et al, 2012;Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Anthraquinones are important phytochemicals in rhubarb and were found to be highly inhibitory for P. gingivalis growth, more specifically aloe-emodin and rhein possessed an MIC of 0.75 mg/ml. The above results are in agreement with previous studies that showed that an anthraquinone-rich extract of another species of rhubarb (Rheum undulatum) exhibited antibacterial activity towards the cariogenic bacterium Streptococcus mutans (Song et al, 2006;Kim et al, 2011). Moreover, synergistic effects of anthraquinones (emodin, rhein) in combination with antibiotics (ampicillin, oxacillin) have been reported for methicillin-resistant Staphylococcus aureus (Joung et al, 2012;Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Chung et al (2006) isolated macelignan from the methanol extract of Myristica fragrans and showed its potent anticariogenic activity against S. mutans and other oral pathogens. The inhibitory activity of methanol extract of Rheum undulatum root against S. mutans and S. sorbinus was investigated by Song et al (2006). The dichloromethane fraction showed the most active antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…on the growth of other Gram-positive bacteria, e.g. Streptococcus mutans and S. sobrinus [9]. It is worth noting that the reported MIC value of plant extracts is often in the range of 100 -1000 mg/mL [30,36].…”
Section: Discussionmentioning
confidence: 99%
“…The use of plants or plant preparations to treat infections has been a common practice in virtually all cultures for a long time [6,7]. Several plant species have been a subject of scientific investigation for many years in order to learn about the biological activity of their compounds, allowing in the future development of alternative, natural antimicrobial compounds [1,2,6,8,9].…”
Section: Introductionmentioning
confidence: 99%